The Translation Of The Names Of Allah Mentioned In The Al-Qur'an Into English. - Al-Bulushi, Saleh Khudabakhsh Hashim (2009)
Allāh revealed the Al-Qur’ān, Muslim holy book, to Prophet Moḥammed (p.b.u.h) in Arabic that is a rich language in Mecca, Arabian Peninsula which is mainly a vast desert with unique geographical, cultural, and climatic features.